Developing a Creative Tourism Process through Cultural Capital to Promote Active Ageing: A Case Study of Noen Hom Community, Prachinburi Province, Thailand - Bunnarong, Somluk; Intavas , Karoon; Sukkasem , Maneerat; Janpong, Wongduan (Area Based Development Research Journal, 2025)
Background Noen Hom Subdistrict in Prachinburi Province, Thailand, is a rural community nestled along the foothills of Khao Yai National Park. The region boasts a rich biocultural landscape, encompassing both natural resources and vibrant cultural heritage. Its cultural capital includes traditional knife forging, herbal processing, angkalung musical instrument craftsmanship, and unique agricultural practices. These elements provide immense potential for developing immersive and creative tourism experiences. However, the community faces socio-demographic shifts, notably an aging population, economic vulnerabilities, and the decline of intergenerational knowledge transfer. This research responds to these challenges by exploring a creative tourism framework rooted in local cultural capital, aiming to promote active aging through a participatory process. Objectives and Methodology The study set out to design and implement a community-based tourism (CBT) model that leverages the cultural and natural assets of Noen Hom, while promoting health, engagement, and self-worth among elderly residents. Grounded in a participatory action research framework, the project followed a seven-phase methodology: 1) Cultural Asset Mapping: Identification and documentation of tangible and intangible local assets. 2) Development of Tourism Routes: Co-creation of tourism circuits highlighting community wisdom and lifestyle. 3) Infrastructure Readiness: Upgrading physical facilities and improving service capabilities. 4) Pilot Route Implementation: Trial operation of planned routes with controlled participant groups. 5) Tourist Engagement: Hosting actual visitor groups to test and refine offerings. 6) Service Evaluation: Gathering feedback from tourists to improve service quality. 7) Dissemination: Use of digital platforms and social media to promote the initiative and scale up the model. Community members, particularly the elderly, were involved at each stage to ensure relevance, ownership, and sustainability. Key Findings and Outcomes 1) Transformation of Elderly Roles. Prior to the project, many elderly community members lived in social and economic dependency with limited social roles. The intervention facilitated a significant transformation in their status. From passive observers, they became cultural leaders—demonstrating traditional crafts, cooking local dishes, and guiding tourists along newly developed routes. Their participation grew from 40 to 80 individuals, with half assuming leadership or facilitative roles. This shift provided a new sense of purpose and revived social identity for the elderly. 2) Economic Empowerment. The economic benefits of the tourism activities, though modest, were meaningful. Elderly participants earned on average over 500 Baht per visitor session through services and product sales. While not a primary income source, this supplement helped reduce family burdens and boosted self-esteem. Fourteen local products—primarily herbal-based goods, handicrafts, and eco-friendly souvenirs—were successfully incorporated into the tourism offerings, adding economic diversity. 3) Community Infrastructure and Capacity Building. Six sites within the subdistrict were enrolled as community tourism destinations. One of them, the multipurpose pavilion at Wat Naprue, was fully upgraded to host tourist and training events, including workshops on artificial flower crafting. In response to infrastructure challenges, the local municipality initiated improvements, including plans to construct two accessible public toilets under the 2026 development budget. Training programs for tourism service delivery were organized, covering local guiding, basic hospitality, video editing with CapCut, and photography. These upskilling sessions led to high visitor satisfaction scores, affirming the quality and professionalism of the services offered. 4) Establishment of Sustainable Structures. To institutionalize the initiative, the community established the "Noen Hom Community Tourism Club," structured similarly to a village administrative committee. With dedicated roles for culinary services, hospitality, finance, music, and overall management, the club set four-year operational terms. Advisory support came from local government authorities and King Mongkut’s University of Technology North Bangkok (Prachinburi Campus). The club has since actively promoted Noen Hom as a creative tourism destination at the provincial level. It has welcomed educational and cultural exchange groups, such as faculty and students from Singapore Polytechnic. Such engagement demonstrates both the project’s scalability and its relevance in broader contexts. Discussion and Implications The results demonstrate the effectiveness of participatory creative tourism as a tool for community revitalization, particularly in aging societies. Through inclusive engagement, the project managed to: 1) Bridge traditional knowledge with modern service practices. 2) Transform elderly residents from dependents into active contributors. 3) Promote sustainable income generation and community pride. 4) Build community-based organizational structures to maintain and scale tourism development. These outcomes align with global frameworks on healthy aging and inclusive development. Moreover, the integration of cultural sustainability and economic empowerment positions the project as a model for similar rural or ethnically diverse communities. Summary This study contributes to a replicable, community-driven tourism framework that fosters active aging, strengthens local identity, and addresses socio-economic vulnerabilities. It underscores the value of using cultural capital not merely for preservation but as a living, evolving resource for sustainable development. Continued investment in community capacity, infrastructure, and intergenerational knowledge exchange will be vital for long-term success.